Parental poison prevention practices and their relationship with perceived toxicity: cross-sectional study. Issue 6 (11th December 2008) - Patel, B; Groom, L; Prasad, V; Kendrick, D
Abstract : Objective: To describe poison prevention practices for a range of substances and explore the relationship between prevention practices and perceptions of toxicity. Design: Cross-sectional study using a validated postal questionnaire. Participants: Parents with children aged 12–35 months on 23 health visitors' caseloads. Setting: Areas of various levels of deprivation in Nottingham, UK. Main outcome measures: Possession and storage of substances, putting substances away immediately after use, and perceptions of toxicity. Results: Dishwasher tablets (68%), toilet cleaner (71%), bleach (74%), oven cleaner (78%), oral contraceptives (80%), and essential oils (81%) were least likely to be stored safely. Children's painkillers (69%), cough medicine (72%), and essential oils (77%) were least likely to be put away immediately after use. More than 50% of parents perceived antibiotics and oral contraceptives as harmful in small quantities and cough medicines as harmful only in large quantities. Six substances perceived by parents to be more harmful were more likely to be put away immediately after use. Parents perceiving dishwasher tablets (OR 1.96, 95% CI 1.05 to 3.66), essential oils (OR 2.80, 95% CI 1.35 to 5.81), turpentine (OR 14.54, 95% CI 2.75 to 76.95), and rat/ant killer (OR 15.33, 95% CI 2.01 to 116.82) as more harmful were more likely to store these substances safely. Conclusions: Parents' perceptions of toxicity of substances were sometimes inaccurate. Perceived toxicity was associated with putting substances away immediately after use for six substances and with safe storage for four substances. The effect of addressing perceptions of toxicity on poison prevention practices requires evaluation.